Study on designing, manufacturing and testing a chilli de-stemming semi-automatic machine - Nguyễn Thanh Phong; Lê Anh Đức; Bùi Ngọc Hùng (Journal of Technical Education Science, 2018)
Study on designing, building and testing a chilli de-stemming semi-automatic machine in production and processing lines of chilli products with the aim of reducing manual labor, production costs and promoting production efficiency in the chilli de-stemming stage. The calculation results have determined the structure and working parameters of the machine with a capacity of 10 ÷ 15kg/hour. Based on the results, the chilli de-stemming semi-automatic machine has been manufactured. The study has demonstrated the de-stemming rate of 88.37%; the damaging rate of 6.34%; the specific power consumption of 20.14Wh/kg and the machine capacity reached 13.89kg/hour at an orientation belt conveyor velocity of 0.13÷ 0.18m/s.The rate between the velocity of de-stemming structure and velocity of orientation conveyor belt is 1.66.